Modern myths, locked minds: secularism and fundamentalism in India - Madan, Triloki N. (Oxford India paperbacks, 2009)
Secularism is one of the important and contentious public debates in India today. It is seen to be in greater crisis now than ever before, making a case for the continuing presence of this book. The debate also furnishes the making of Indian polity and society, given the inter-related development of culture, society and politics in India. It is thus a debate about religious nationalism and fundamentalism as well. Modern Myths, Locked Minds examines the ideologies of secularism and fundamentalism in the setting of the religious traditions of India--Hinduism, Sikhism, and Islam. Further insightful comparison of the traditions is offered, each seen over a long period of time, revealing markedly distinctive historical experiences